2010
DOI: 10.1111/j.1476-5829.2010.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased monocyte chemotactic protein‐1 concentration and monocyte count independently associate with a poor prognosis in dogs with lymphoma

Abstract: Overexpression of the chemokine monocyte chemotactic protein-1 (MCP-1) has been associated with a poor prognosis in many human cancers. Increased MCP-1 concentrations may promote tumour progression by increasing mobilization of myeloid derived suppressor cells such as immature monocytes and neutrophils. We hypothesized that increased numbers of peripheral neutrophils or monocytes and increased MCP-1 concentrations would predict a worse outcome in dogs with multicentric lymphoma. In this retrospective study inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
73
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 26 publications
5
73
2
Order By: Relevance
“…Both innate and adaptive immune cells can be altered during cancer and the contribution of dysregulated myeloid cells is increasingly being recognized in humans and mice with cancer (Mantovani et al, 2010; Schmid and Varner, 2010; Yang and Carbone, 2004). This study showed that canine tumor cells affect canine myeloid cell function, which may explain the findings that increased myeloid cells or myeloid cell markers are negative prognostic indicators (Perry et al, 2011; Sottnik et al, 2010). It is possible that these dogs with cancer were less able to generate anti-tumor immunity, even in the presence of elevated myeloid cell numbers, due to suppressive or dysfunctional myeloid cells.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Both innate and adaptive immune cells can be altered during cancer and the contribution of dysregulated myeloid cells is increasingly being recognized in humans and mice with cancer (Mantovani et al, 2010; Schmid and Varner, 2010; Yang and Carbone, 2004). This study showed that canine tumor cells affect canine myeloid cell function, which may explain the findings that increased myeloid cells or myeloid cell markers are negative prognostic indicators (Perry et al, 2011; Sottnik et al, 2010). It is possible that these dogs with cancer were less able to generate anti-tumor immunity, even in the presence of elevated myeloid cell numbers, due to suppressive or dysfunctional myeloid cells.…”
Section: Discussionmentioning
confidence: 54%
“…Recent work in dogs suggests that peripheral blood myeloid cell populations (e.g. monocytes and neutrophils) may be a prognostic indicator in canine cancer and that canine myeloid cells may be useful for canine cancer vaccines but, at present, the effects of cancer on canine myeloid cell responses has not been studied (Bird et al, 2008; Perry et al, 2011; Sottnik et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Prognostic factors in other canine studies of multicentric lymphoma have included sex [78], [79], B or T immunophenotype [53], [80]–[82], stage [81], [83][85], substage [79], [83], serum calcium concentration [86], packed cell volume [87], monocyte concentration [88], prior administration of corticosteroids [89], [90], treatment protocol [62], [91], coagulation profile [92], presence of minimal residual disease after treatment [93], and cytomorphological and histopathological characteristics [56], [61], [62], [81]. However, in common with our own observations, different studies have yielded different conclusions and have not all been able to demonstrate a prognostic impact of every one of the examined variables: factors such as the number and clinical heterogeneity of recruited patients and the nature of the specific end points examined influence the results of such outcome analyses [94].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, elevated serum MCP-1 concentrations were associated with decreased disease-free intervals in lymphoma dogs treated by chemotherapy [12]. These reports suggest that MCP-1 may be available as prognostic indicators of IMHA and lymphoma in dogs, moreover, this may be true of some other diseases.…”
mentioning
confidence: 82%